Multi-arm ionic liquid crystals formed by cholesteric mesophase and pyridinium groups. Issue 8 (21st June 2019) - Tang, Xinqiao; Bai, Lu; Kong, Shengwen; Wang, Xiaodong; Meng, Fanbao
ABSTRACT: A series of novel star-shaped ionic liquid crystals (ILCs) compounds with various counterions (derived from HBF4, HPF6, CF3 COOH, d-MH-SO3 H, H3 PO4, p-Toluenesulfonic acid) were designed and synthesised starting from precursors of pyridines and liquid crystalline monomer cholesteryl 4-bromobutanoate. Inducing various counterions by use of ionic self-assembly due to electrostatic attraction of various ion clusters was one of the most essential factors for intermolecular separation. The chemical structures, liquid crystalline properties, self-assembly behaviour and ionic conductivity of these compounds were researched during multiple experimental techniques. The star-shaped ILCs showed a smectic A (SmA) mesophase. The d-spacing of star-shaped ILCs increased slightly due to the increase volume of anion. The clearing temperatures of the pyridinium salts suggested that the effect of the stabilisation on the SmA structures was in the order H2 PO4 − >BF4 − >TS − >D-MH-SO3 − >CF3 COO − >PF6 − . All these star-shaped ILCs displayed ionic conductivity in mesophase. It was noted that the conductivity (σ) increased with the increase of the anion size and temperature. Graphical Abstract: